2012
DOI: 10.1111/imm.12005
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin modulates the conversion of human CD4+ CD25T cell to CD4+ CD25+ FOXP3+T cell via suppressing interleukin‐10‐producing regulatory T cell

Abstract: SummaryBecause regulatory T (Treg) cells play an important role in modulating the immune system response against both endogenous and exogenous antigens, their control is critical to establish immunotherapy against autoimmune disorders, chronic viral infections and tumours. Ribavirin (RBV), an antiviral reagent used with interferon, is known to polarize the T helper (Th) 1/2 cell balance toward Th1 cells. Although the immunoregulatory mechanisms of RBV are not fully understood, it has been expected that RBV wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…To differentiate between different scenarios for the origin of non-Gaussianity we should examine further the statistics of the primordial density field. For example, in the absence of curvaton self-interactions the scale-dependence of the non-linearity parameter is given by [13,[37][38][39] n fNL ≡ ∂ ln |f NL | ∂ ln k = 2(n σ − 1) − 2(n ζ − 1) = 2(1 − w χ )(n χ − n φ ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To differentiate between different scenarios for the origin of non-Gaussianity we should examine further the statistics of the primordial density field. For example, in the absence of curvaton self-interactions the scale-dependence of the non-linearity parameter is given by [13,[37][38][39] n fNL ≡ ∂ ln |f NL | ∂ ln k = 2(n σ − 1) − 2(n ζ − 1) = 2(1 − w χ )(n χ − n φ ) .…”
Section: Discussionmentioning
confidence: 99%
“…The second inflaton slow-roll parameter, η, then affects only the scale-dependence of the power spectrum. Very recently Kobayashi and Takahashi have considered the scale-dependence of both the power spectrum and the non-Gaussianity including mixed inflaton-curvaton models [13]. Note that Langlois and Vernizzi [14] studied linear adiabatic and isocurvature density perturbations allowing for a general inflaton potential, which was then extended [15] to second-and higher-order to study non-Gaussianity in both adiabatic and residual isocurvature density perturbations after inflation and their correlation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed the critical roles of IL-10 and TGF-b in the development of Tregs (44,45). Moreover, some evidence showed that IL-10 was an important factor in the resolution of ALI (46,47).…”
Section: Macrophages Induced the Proliferation Of Tregs Through Il-10mentioning
confidence: 98%
“…ϩ adaptive Treg cells to maintain Th1 cell activity (32). The role of the ribavirin-induced immune response in acting as a selective pressure on hantaviral population and evolution has not yet been addressed.…”
mentioning
confidence: 99%